2013
DOI: 10.1016/j.molcel.2013.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Reinitiation and Other Unconventional Posttermination Events during Eukaryotic Translation

Abstract: During ribosome recycling, post-termination complexes are dissociated by ABCE1 and eRF1 into 60S and tRNA/mRNA-associated 40S subunits, after which tRNA/mRNA are released by eIF1/eIF1A, Ligatin or MCT1/DENR. In some instances, 40S subunits remain associated with mRNA and reinitiate at nearby AUGs. Here, we recapitulated reinitiation in vitro using a reconstituted mammalian translation system. The presence of eIFs 2/3/1/1A and Met-tRNAiMet was sufficient for recycled 40S subunits to remain on mRNA, scan bidirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
172
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(189 citation statements)
references
References 52 publications
10
172
1
Order By: Relevance
“…In eukaryotes (humans and mice), translation of approximately half of the transcripts are regulated by short upstream ORFs (uORFs) (62,63) and translation of the downstream ORF requires reinitiation. Recently, it was shown that after a termination event, 40S subunits, and probably also 80S ribosomes, could scan along the mRNA downstream or upstream to the next AUG position (64). Ribosome profiling methodology also revealed the possibility that 80S ribosomes scan downstream after translating a cistron in yeast (65).…”
Section: Discussionmentioning
confidence: 99%
“…In eukaryotes (humans and mice), translation of approximately half of the transcripts are regulated by short upstream ORFs (uORFs) (62,63) and translation of the downstream ORF requires reinitiation. Recently, it was shown that after a termination event, 40S subunits, and probably also 80S ribosomes, could scan along the mRNA downstream or upstream to the next AUG position (64). Ribosome profiling methodology also revealed the possibility that 80S ribosomes scan downstream after translating a cistron in yeast (65).…”
Section: Discussionmentioning
confidence: 99%
“…26,95 To get further insight into the involvement of ABCE1 in cell proliferation, we considered its potential role in the synthesis of proteins essential for cell cycle progression. The translation of certain transcripts is highly dependent on the initiation step, which is determined by both the activity of initiation factors and the 5 0 -UTR structure of mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Reinitiation of translation refers to the mechanism that allows the ribosome to bind and initiate at a downstream start codon after a stop codon has been met upstream [32][33][34][35] and reviewed in Jackson et al 36 A substantial number (445%) of mammalian genes contain at least one short upstream ORF (upORF) preceding the coding domain of the gene. 34,36 The process of reinitiation is often inefficient.…”
Section: Discussionmentioning
confidence: 99%